Comparative Efficacy of Single Pill Combinations of Azilsartan Medoxomil/Chlorthalidone and Losartan/Hydrochlorothiazide in Patients with Hypertension and Heart Failure with Preserved Ejection Fraction - Zh. D. Kobalava; A. F. Safarova; Kh. M. Gudieva; M. A. Markova; A. E. Petrosyan (Столичная издательская компания, 2022)
Aim. To study the effects of azilsartan medoxomil/chlorthalidone (AZM/CTD) and losartan/hydrochlorothiazide (LOS/HCT) combinations for NTproBNP levels, 6-minute walk test results, hydration status along with their antihypertensive efficacy according to clinical and 24-hour blood pressure in patients with hypertension and heart failure with preserved ejection fraction (HFpEF).Material and methods. An open randomized study included 56 patients with uncontrolled or untreated hypertension and HFpEF. Patients randomized to receive the AZM/CTD 40/12.5 mg/day (group 1; n=28) or LOS/HCT 100/12.5 (group 2; n=28) within 4 weeks. Patients who did not achieve the target BP <140/<90 mm Hg study drug dose was intensified: in the first group, an increase in the dose of AZM/CTD 40/25 mg/day, in the second group, an increase in the dose of LOS/HCT 100/25 mg/day. The observation period was 12 weeks. All patients underwent a clinical examination with an assessment of symptoms and/or signs of HF, laboratory and instrumental studies, including NT-proBNP, ambulatory blood pressure (BP) monitoring, applanation tonometry, a 6-minute walk test (6MWT), echocardiography. In order to assess the status of hydration, bioimpedance vector analysis (BIVA) was performed. HFpEF was diagnosed according to the HFA-PEFF algorithm. The results were considered statistically significant at p<0.05.Results. After 12 weeks, 92% of patients in the first and 78% of patients in the second group reached the target clinical BP (р<0,05). Average daily BP <130/ <80 mm Hg was reached by 82% of patients treated with the combination of AZM/CTD, compared with 67% treated with the combination of losartan/HCT (p<0.05). After 12 weeks, patients from both groups showed a significant decrease in systolic and diastolic blood pressure, central blood pressure, and a decrease in pulse wave velocity, which was more significantly significant in the first group of patients (p<0.05). During therapy in both groups of patients, a significant decrease in the level of NT-proBNP was observed: in the first group from 300 [199; 669] pg/ml to 156 [157; 448] pg/ml (p=0,003), in the second group from 298 [180; 590] pg/ml to 194 [140; 360] pg/ml (p=0,006), an increase in the distance during the 6MWT from 317 [210; 398] m to 380 [247; 455] m (p=0,006) in in the first group and an improvement in the hydration status according to the BIA data, but more significantly significant in the first group (p<0.001).Conclusion. In patients with hypertension and HFpEF, therapy with the AZM/CTD combination compared with LOS/HCT is accompanied by a more pronounced antihypertensive effect in terms of ambulatory and peripheral blood pressure, central blood pressure, NTproBNP levels, increased distance in 6MWT and achievement of euvolemia status.